Vestibulo-Cerebellar Disease Impairs the Central Representation of Self-Orientation - Tarnutzer, Alexander A.; Shaikh, Aasef G.; Palla, Antonella; Straumann, Dominik; Marti, Sarah (Frontiers in Neurology, 2011)
Transformation of head-fixed otolith signals into a space-fixed frame of reference is essential for perception of self-orientation and ocular motor control. In monkeys the nodulus and ventral uvula of the vestibulo-cerebellum facilitate this transformation by computing an internal estimate of direction of gravity. These experimental findings motivated the hypothesis that degeneration of the vestibulo-cerebellum in humans alter perceptual and ocular motor functions that rely on accurate estimates of gravity, such as subjective visual vertical (SVV), static ocular counterroll (OCR), and gravity-dependent modulation of vertical ocular drifts. We assessed the SVV, OCR, and spontaneous vertical ocular drifts in 12 patients with chronic vestibulo-cerebellar disease and in ten controls. Substantially increased variability in estimated SVV was noted in the patients. Furthermore, gravity-dependent modulation of spontaneous vertical ocular drifts along the pitch plane was significantly (p < 0.05) larger in the patients. However, the gain and variability of static OCR and errors in SVV were not significantly different. In conclusion, in chronic vestibulo-cerebellar disease SVV and OCR remain intact except for an abnormal variability in the perception of verticality and impaired stabilization of gaze mediated by the otoliths. These findings suggest that OCR and perceived vertical are relatively independent from the cerebellum unless there is a cerebellar imbalance like an acute unilateral cerebellar stroke. The increased trial-to-trial SVV variability may be a general feature of cerebellar disease since a function of the cerebellum may be to compensate for such. SVV variability might be useful to monitor disease progression and treatment response in patients.